Incidencia de un sistema informático en la gestión de la información médica y control de historias clínicas del Gobierno Autónomo Descentralizado provincial de Napo - Yanza Lucio, Jeferson Paúl (2017)
The present investigation determined the impact that a Computer System has on the management of medical information and control of clinical records of the Autonomous Government of Napo Provincial Decentralized in 2017. The hypothesis raised in the research was: The use of a computer system will improve the administration of clinical records in the Autonomous Government Decentralized Provincial Napo. The instruments for obtaining data were interviews, surveys and direct observation directed to the community that make up the Medical Dispensary Unit. With the information collected, it was possible to determine the difficulties presented by the management of medical information, which was relevant for the development of the computer system. The agile methodology for the software development process used was Rapid Application Development (RAD). With the implementation of the Computer System, the hypothesis that was presented in this research project, which considerably improved the management of information, streamlined the processes of registration and search of patients and clinical histories. It minimized the inconsistency of information generated by human errors, mainly benefiting medical care for the servers and servers of the Autonomous Government Decentralized Napo Provincial and their families. Keywords: Management, Processes, Development, Computer system